To What Extent Do Free Healthcare Policies and Performance-Based Financing Reduce Out-of-Pocket Expenditures for Outpatient services? Evidence From a Quasi-experimental Study in Burkina Faso - Thit Thit Aye; Hoa Thi Nguyen; Stephan Brenner; Paul Robyn; Ludovic Tapsoba; Julia Lohmann; Manuela De Allegri (Kerman University of Medical Sciences, 2023)
Background  Burkina Faso has been implementing financing reforms towards universal health coverage (UHC) since 2006. Recently, the country introduced a performance-based financing (PBF) program as well as user fee removal (gratuité) policy for health services aimed at pregnant and lactating women and children under 5. We aim to assess the effect of gratuité and PBF policies on facility-based out-of-pocket expenditures (OOPEs) for outpatient services.Methods  Our study is a controlled pre- and post-test design using healthcare facility data from the PBF program's impact evaluation collected in 2014 and 2017. We compared OOPE related to primary healthcare use incurred by children under 5 and individuals above 5 to assess the effect of the gratuité policy on OOPE. We further compared OOPE incurred by individuals residing in PBF districts and non-PBF districts to estimate the effect of the PBF on OOPE. Effects were estimated using difference-in-differences models, distinguishing the estimation of the probability of incurring OOPE from the estimation of the magnitude of OOPE using a generalized linear model (GLM).Results  The proportion of children under 5 incurring OOPE declined significantly from 90% in 2014 to 3% in 2017. Concurrently, mean OOPE also decreased. Differences in both the probability of incurring OOPE and mean OOPE between PBF and non-PBF facilities were small. Our difference in differences estimates indicated that gratuité produced an 84% (CI -86%, -81%) reduction in the probability of incurring OOPE and reduced total OOPE by 54% (CI 63%, 42%). We detected no significant effects of PBF, either in reducing the probability of incurring OOPE or in its magnitude.Conclusion  User fee removal is an effective demand-side intervention for enhancing financial accessibility. As a supplyside intervention, PBF appears to have limited effects on reducing financial burden.